Comparison of Multisegmental Foot and Ankle Motion Between Total Ankle Replacement and Ankle Arthrodesis in Adults. (September 2017) - Seo, Sang Gyo; Kim, Eo Jin; Lee, Doo Jae; Bae, Kee Jeong; Lee, Kyoung Min; Lee, Dong Yeon
Background: Total ankle replacement (TAR) and ankle arthrodesis (AA) are usually performed for severe ankle arthritis. We compared postoperative foot segmental motion during gait in patients treated with TAR and AA. Methods: Gait analysis was performed in 17 and 7 patients undergoing TAR and AA, respectively. Subjects were evaluated using a 3-dimensional multisegmental foot model with 15 markers. Temporal gait parameters were calculated. The maximum and minimum values and the differences in hallux, forefoot, hindfoot, and arch in 3 planes (sagittal, coronal, transverse) were compared between the 2 groups. One hundred healthy adults were evaluated as a control. Results: Gait speed was faster in the TAR ( P = .028). On analysis of foot and ankle segmental motion, the range of hindfoot sagittal motion was significantly greater in the TAR (15.1 vs 10.2 degrees in AA; P = .004). The main component of motion increase was hindfoot dorsiflexion (12.3 and 8.6 degrees). The range of forefoot sagittal motion was greater in the TAR (9.3 vs 5.8 degrees in AA; P = .004). Maximum ankle power in the TAR (1.16) was significantly higher than 0.32 in AA; P = .008). However, the range of hindfoot and forefoot sagittal motion was decreased in both TAR and AA compared with the control group ( P = .000). Conclusion: Although biomechanical results of TAR and AA were not similar to those in the normal controls, joint motions in the TAR more closely matched normal values. Treatment decision making should involve considerations of the effect of surgery on the adjacent joints. Level of Evidence: Level III, case-control study.